2020
DOI: 10.1302/2633-1462.17.bjo-2020-0025.r1
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient and outpatient opioid requirements after total joint replacement are strongly influenced by patient and surgical factors

Abstract: Aims Currently, there is no single, comprehensive national guideline for analgesic strategies for total joint replacement. We compared inpatient and outpatient opioid requirements following total hip arthroplasty (THA) versus total knee arthroplasty (TKA) in order to determine risk factors for increased inpatient and outpatient opioid requirements following total hip or knee arthroplasty. Methods Outcomes after 92 primary total knee (n = 49) and hip (n = 43) arthroplasties were analyzed. Patients with repeat s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 43 publications
3
8
0
Order By: Relevance
“…35,37 OTHER Other factors contributing to increased opioid use include specific characteristics of the surgery such as operative time and patient pain in the immediate postoperative period. 24,[42][43][44][45] Cao et al showed that longer operative times were independently associated with increased opioid use, which correlate with the previous findings of Polizer et al 24,43 Increased pain on post-operative day one and increased opioid utilization in the 24-hours before hospital discharge are also independent predictors of prolonged opioid use following TKA. 42,44,45…”
Section: Socioeconomic Factors and Medical Comorbiditiessupporting
confidence: 61%
See 1 more Smart Citation
“…35,37 OTHER Other factors contributing to increased opioid use include specific characteristics of the surgery such as operative time and patient pain in the immediate postoperative period. 24,[42][43][44][45] Cao et al showed that longer operative times were independently associated with increased opioid use, which correlate with the previous findings of Polizer et al 24,43 Increased pain on post-operative day one and increased opioid utilization in the 24-hours before hospital discharge are also independent predictors of prolonged opioid use following TKA. 42,44,45…”
Section: Socioeconomic Factors and Medical Comorbiditiessupporting
confidence: 61%
“…24,[42][43][44][45] Cao et al showed that longer operative times were independently associated with increased opioid use, which correlate with the previous findings of Polizer et al 24,43 Increased pain on post-operative day one and increased opioid utilization in the 24-hours before hospital discharge are also independent predictors of prolonged opioid use following TKA. 42,44,45…”
Section: Socioeconomic Factors and Medical Comorbiditiessupporting
confidence: 61%
“…[52][53][54] In addition, younger and unemployed individuals were found to be more likely to need greater opioid quantities in the post-operative period compared to older individuals or those with employment. 55 Additionally, Medicare patients were found to be more likely to demonstrate chronic opioid use in contrast to their non-Medicare counterparts. 56 OTHER Many medical comorbidities afflicting patients undergoing THA are associated with increased post-operative opioid utilization.…”
Section: Pre-operative Opioid Usementioning
confidence: 99%
“…Certain comorbidities that have been linked with increased opioid use after THA include mental health disorders, diabetes, hypertension, chronic pulmonary disease, chronic kidney disease, acquired immunodeficiency syndrome (AIDS), peripheral vascular disease, chronic nonspecific pain, and substance abuse. 51,52,54,55 History of prior hospital complications is also associated with increased post-operative opioid use. 50 In addition, patients who have inferior health statuses pre-operatively, denoted by an ASA score over 2, have been found to have inferior outcomes with regards to chronic opioid use.…”
Section: Pre-operative Opioid Usementioning
confidence: 99%
“…Preoperative opioid use is the strongest and most consistent predictor of postoperative opioid use while other factors continue to be debated [ [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ]. Black race, chronic pulmonary disease, anxiety, substance abuse, and back pain were found in 1 study to be risk factors for increased postoperative opioid use [ 23 ].…”
Section: Introductionmentioning
confidence: 99%